The Effect of Auditor Competence on Audit Quality at The Regional Inspectorate of Garut Regency - Riskia, Tenia Gusmiliani; Wahyuningsih, Wahyuningsih; Ungkari, Marti Dewi (Fakultas Ekonomi Universitas Garut, 2023)
The study aims to evaluate the impact of auditor competence on audit quality at the Regional Inspectorate of Garut Regency. A quantitative method with descriptive and associative approaches was used in this research. Data collection was carried out through literature review as well as field surveys using questionnaires and interviews. For data analysis, simple linear regression techniques and coefficient of determination analysis were employed. The study reveals that auditor competence has a significant impact on audit quality at the Regional Inspectorate of Garut Regency.